Analysis of the Relevance of Ibnu Miskawaih's Islamic Educational Philosophy Theory in Vocational Secondary Schools - Fahlawi, Sahrizal (LPPM Universitas PGRI Sumatera Barat, 2023)
This paper discusses the philosophical thinking of Islamic religious education of Ibn Miskawaih, then the researcher tries to analyze how the relevance and implementation of the theory is at SMK Anak Bangsa School in Central Lombok Regency. Field facts show that SMK Anak Bangsa School is a school that in principle is able to implement Islamic Religious Education learning optimally, both directed at the learning curriculum, learning methods, and implementation of Islamic educational values in the context of experience-based learning and several relevant researcher findings. Based on the academic problems above, the researcher sees an integration-interconnection, namely between the relevance and implementation of the philosophical thinking of Islamic education of Ibn Miskawaih towards education at SMK Anak Bangsa School. To limit the problems of this research, the researcher highlights several important aspects including, First, How is the concept of Islamic educational philosophy from Ibn Miskawaih's perspective. Second, How is the relevance between Islamic educational thinking and learning at SMK Anak Bangsa School, then the researcher analyzes the suitability of the theory with the implementation of learning at the School. This research is based on a descriptive qualitative approach. The analysis method used in this study is data that is analyzed descriptively qualitatively using various theoretical foundations related to the object of research and used as a basic reference for qualitative analysis because it is inseparable from observation, interviews, and documentation. Based on the findings of the researcher, Ibn Miskawaih Islamic educational philosophy emphasizes more on the aspect of moral formation, then forms experiences by actualizing education based on Islam to realize the values of faith and Islam. Then the relevance and implementation at SMK Anak Bangsa School are reflected in several religious practices both in formal and non-formal activities. As with reading the Qur'an, practicing morals and ethics between teachers and students, and several developments in learning activities outside of school to introduce the values of moral education in life, especially in the field of Islamic education at SMK Anak Bangsa School.